Nginig (ABS-CBN, 2004)
Pagbabalik sa guho : a storm revanges the residents of San Francisco Leyte. But even beyond death, three souls prove that promises are mean to be kept. A bride comes back from the dead to ease her beloved's pain... A woman's ghost 'Wathces over' her friends sari-sari store, keeping strangers out.